Physiological, Biochemical, and Root Proteome Networks Revealed New Insights Into Salt Tolerance Mechanisms in Pongamia pinnata (L.) Pierre - Marriboina, Sureshbabu; Sekhar, Kalva Madhana; Subramanyam, Rajagopal; Reddy, Attipalli Ramachandra (Frontiers in Plant Science, 2022)
Cultivation of potential biofuel tree species such as Pongamia pinnata would rehabilitate saline marginal lands toward economic gains. We carried out a physiological, biochemical, and proteomic analysis to identify key regulatory responses which are associated with salt tolerance mechanisms at the shoot and root levels. Pongamia seedlings were grown at 300 and 500 mM NaCl (∼3% NaCl; sea saline equivalent) concentrations for 15 and 30 days, gas exchange measurements including leaf net photosynthetic rate (Asat), stomatal conductance (gs), and transpiration rate (E), and varying chlorophyll a fluorescence kinetics were recorded. The whole root proteome was quantified using the free-labeled nanoLC-MS/MS technique to investigate crucial proteins involved in signaling pathways associated with salt tolerance. Pongamia showed no visible salt-induced morphological symptoms. However, Pongamia showed about 50% decline in gas exchange parameters including Asat, E, and gs 15 and 30 days after salt treatment (DAS). The maximum potential quantum efficiency of photosystem (PS) II (Fv/Fm) was maintained at approximately 0.8 in salt-treated plants. The thermal component of PSII (DIo) was increased by 1.6-fold in the salt-treated plants. A total of 1,062 protein species were identified with 130 commonly abundant protein species. Our results also elucidate high abundance of protein species related to flavonoid biosynthesis, seed storage protein species, and carbohydrate metabolism under salt stress. Overall, these analyses suggest that Pongamia exhibited sustained leaf morphology by lowering net photosynthetic rates and emitting most of its light energy as heat. Our root proteomic results indicated that these protein species were most likely recruited from secondary and anaerobic metabolism, which could provide defense for roots against Na+ toxicity under salt stress conditions.